Design of Geraniol-Loaded Nanocapsules for Use Against Salmonella Infantis: Evaluation in an In Vitro Poultry Model - Karla S. Garcia-Salazar; Hector J. Leon-Solano; Jesus A. Maguey-Gonzalez; Juan D. Latorre; Raquel López-Arellano; Elvia A. Morales Hipólito; Roberto Díaz-Torres; Miguel Morales Rodríguez; Alma Vázquez-Durán; Guillermo Tellez-Isaias; Abraham Méndez-Albores; Bruno Solis-Cruz; et al. (Pharmaceutics, 2025)
Background/Objectives: Salmonella Infantis (S. Infantis) is a bacterium that has gained importance in public health over the last decade due to its high pathogenicity and resistance to antibiotics. Therefore, the objective of the present study was to present key considerations for the design and development of geraniol-loaded nanocapsules for its delivery in the drinking water or feed of broiler chickens and to evaluate its potential as an antimicrobial agent against S. Infantis using a standard in vitro microplate assay and a model that simulates the pH and feed conditions of the crop of broiler chickens. Methods: Using a 3k factorial experimental design, geraniol nanocapsule-based formulations were selected, and their antimicrobial activity was evaluated in in vitro models. Results: The results demonstrated that geraniol alone exhibits antimicrobial action against S. Infantis mainly due to its lipophilicity, hydrophobicity and the presence of the hydroxyl group found in its chemical structure, but when formulated in nanocapsular systems, the interaction of its components tends to reduce its antimicrobial action, especially the mixture of Tween 80:Span 80 and Miglyol® 810N. Furthermore, the use of the in vitro model that simulates the crop of broiler chickens demonstrated that the formulation also has interactions with the feed components, completely nullifying the antimicrobial action of geraniol compared to that obtained in the in vitro microplate model. Conclusions: Preformulation studies during the development of nanocapsule-based formulations should be considered for the correct selection of the components of a formulation to ensure its effectiveness, without only considering the physicochemical and stability properties of these as is frequently seen in studies.